Photovoltaic High-Frequency Pulse Charger for Lead-Acid Battery under Maximum Power Point Tracking - Hung-I. Hsieh; Sheng-Fang Shih; Jen-Hao Hsieh; Chi-Hao Wang (International Journal of Photoenergy)
A photovoltaic pulse charger (PV-PC) using high-frequency pulse train for charging lead-acid battery (LAB) is proposed not only to explore the charging behavior with maximum power point tracking (MPPT) but also to delay sulfating crystallization on the electrode pores of the LAB to prolong the battery life, which is achieved due to a brief pulse break between adjacent pulses that refreshes the discharging of LAB. Maximum energy transfer between the PV module and a boost current converter (BCC) is modeled to maximize the charging energy for LAB under different solar insolation. A duty control, guided by a power-increment-aided incremental-conductance MPPT (PI-INC MPPT), is implemented to the BCC that operates at maximum power point (MPP) against the random insolation. A 250 W PV-PC system for charging a four-in-series LAB (48 Vdc) is examined. The charging behavior of the PV-PC system in comparison with that of CC-CV charger is studied. Four scenarios of charging statuses of PV-BC system under different solar insolation changes are investigated and compared with that using INC MPPT.